Autism Spectrum Disorders (ASD) - Searching for the Biological Basis for Behavioral Symptoms and New Therapeutic Targets - Benjamin Gesundheit (Frontiers Research Topics, 2017)
Autism Spectrum Disorder (ASD) is currently diagnosed based on a series of behavioral tests. The challenge for researchers is to try to uncover the biological basis for these typical behaviors in order to improve diagnosis and identify potential targets for treatment. A multidisciplinary approach is necessary in order to move forward. This includes analysis of the current animal models for ASD and their suitability, reviewing immunological, immunogenetic and epigenetic research, reassessing clinical diagnostic tools, and surveying radiological, pathological, and serological records for clues. This volume includes research from some of the leading researchers on ASD. We are hopeful that it will stimulate further dialogue and research in this challenging field.